PROSES DAN TANTANGAN PENGAMBILAN KEPUTUSAN DALAM SISTEM PEMERINTAHAN GEREJA PRESBITERIAN SINODAL - Luma, Subaedah; Matheos, Frigita Ekasari; Andalangi, Julinda Ahtri; Panawar, Jesica (Theosebia: Jurnal Teologi, Pendidikan Agama Kristen dan Psikospiritual, 2024)
This study aims to analyze the Presbyterian church governance system, focusing on its structure, advantages, and challenges encountered in decision-making processes. The Presbyterian governance system involves the election of elders from local churches who form a session, with the pastor holding equal authority as a member of the session. This session manages the local church’s activities, while elders are also part of a presbytery and a general assembly with broader authority. The research employs a qualitative approach using literature analysis and case observations to understand the dynamics of church governance within a Presbyterian context. Findings indicate that the system supports wise leadership and church unity but faces challenges when decisions are influenced by financial power, leading to potential injustice and conflicts. The study’s benefits include a deeper understanding of how this system operates in practice and recommendations for improving conflict management and decision-making. The conclusion emphasizes the need for transparency, leadership training, and the establishment of advisory boards to ensure that church decisions reflect the needs of the entire congregation, rather than the interests of financially influential individuals.